Simvastatin reduces vaso‐occlusive pain in sickle cell anaemia: a pilot efficacy trial. (28th March 2017) - Hoppe, Carolyn; Jacob, Eufemia; Styles, Lori; Kuypers, Frans; Larkin, Sandra; Vichinsky, Elliott
Summary: Sickle cell anaemia (SCA) is a progressive vascular disease characterized by episodic vaso‐occlusive pain. Despite the broad impact of inflammation on acute and chronic clinical manifestations of SCA, no directed anti‐inflammatory therapies currently exist. Statins are cholesterol‐lowering agents shown to confer protection from vascular injury by suppressing inflammation. We previously documented a reduction in soluble biomarkers of inflammation in patients with sickle cell disease treated with simvastatin. To determine the potential clinical efficacy of simvastatin, we treated 19 SCA patients with single daily dose simvastatin for 3 months and assessed changes from baseline in the frequency and intensity of diary‐reported pain and levels of circulating nitric oxide metabolites (NOx), high sensitivity C‐reactive protein (hs‐CRP), vascular cell adhesion molecule 1 (VCAM‐1), intercellular adhesion molecule 1 (ICAM‐1), ICAM‐3, E‐selectin, and vascular endothelial growth factor (VEGF). Treatment with simvastatin resulted in a significant reduction in the frequency of pain ( P = 0·0003), oral analgesic use ( P = 0·003) and circulating hs‐CRP ( P = 0·003), soluble (s)E‐selectin ( P = 0·01), sICAM‐1 ( P = 0·02), sICAM‐3 ( P = 0·02) and sVEGF ( P = 0·01). Simvastatin had no effect on pain intensity or levels of NOx, sP‐selectin and sVCAM‐1. The observed reductions in pain rate and markers of inflammation were greatest in subjects receiving hydroxycarbamide (HC), suggesting a synergistic effect of simvastatin. These results provide preliminary clinical data to support a larger trial of simvastatin in SCA.